Response of People Living with HIV-AIDS to HIV-AIDS Stigma in Kupang City - Henny Saranike Laure; Anna Henny Talahatu; Rut Rosina Riwu (Media Kesehatan Masyarakat, 2022)
HIV-AIDS is a dangerous disease in society. In Indonesia, people living with HIV-AIDS are still considered a disgrace, so that stigma appears in society which makes people living with HIV feel pessimistic in living their lives, mentally and psychologically being depressed by the stigma. The purpose of this study was to determine the knowledge, attitudes, and actions of PLWHA on the stigma of HIV-AIDS in Kupang City in 2019. The research design used in this study was descriptive qualitative. The research was conducted by in-depth interviews with 6 informants using interview guidelines. The results showed that the informants had good knowledge about stigma because the informants had understood correctly that the bad treatment from family, neighbors, and health workers that the informants had received in their daily life was a stigma. Informants try to accept the stigma from neighbors and health workers positively because they are supported by the closest people and choose to continue taking treatment at health facilities for the survival of PLWHA. People living with HIV-AIDS continue to take ARVs and carry out activities like society in general. The hope of PLWHA related to stigma in this study is to reduce stigma and increase knowledge about HIV/AIDS and increase awareness of the health team and the community about the importance of caring for people with HIV-AIDS.